An Increase in TNF-α Levels in Fetus due to Prenatal Ischemic Hypoxia - Indriawati, Ratna; Risdiana, Nurvita; Wibowo, Tunjung (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Prenatal ischemic hypoxia can increase mortality and morbidity and affect the immune system. One of the immune responses is tumor necrosis factor-α (TNF-α) levels. However, the cellular mechanism of immune response abnormalities due to prenatal hypoxia remains unclear. An 11–17-day-old fetus is a sensitive period of neural development. Brain ischemia will cause cell dysfunction and can even affect TNF-α levels. Thus, how prenatal ischemic hypoxia increases TNF-α levels in the fetus remains unclear. AIM: This study aims to examine the effect of the onset and duration of prenatal ischemic hypoxia on TNF-α levels. METHODOLOGY: An experimental study with a post-test control design was conducted. Thirty Rattus norvegicus were induced with prenatal ischemic hypoxia (embryos aged 7, 12, and 17 days). The independent variable was prenatal ischemic hypoxia, while the dependent variable was TNF-α levels. TNF-α was measured using the ELISA technique and was carried out when the fetus was 19 days old (E19). The TNF-α was analyzed using ANOVA, and the limit of significance was set at p < 0.05. RESULTS: The TNF-α levels in the prenatal ischemic hypoxia group were statistically higher than in the control group (p < 0.05). The more the onset and the longer the ischemic hypoxia is, the higher the TNF-level (p < 0.05). CONCLUSION: The prenatal ischemic hypoxia increased TNF-α levels in the fetus.